Mostly harmless econometrics an empiricist's companion - Angrist, Joshua David; Pischke, Jorn-Steffen (Princeton University Press, 2009)
"In addition to econometric essentials, this book covers important new extensions as well as how to get standard errors right. The authors explain why fancier econometric techniques are typically unnecessary and even dangerous."--Provided by publisher.